The Running Athlete: Stress Fractures, Osteitis Pubis, and Snapping Hips - Henning, P. Troy (SAGE Publications, 2014)
CONTEXT: Pelvic stress fractures, osteitis pubis, and snapping hip syndrome account for a portion of the overuse injuries that can occur in the running athlete. EVIDENCE ACQUISITION: PubMed searches were performed for each entity using the following keywords: snapping hip syndrome, coxa sultans, pelvic stress fracture, and osteitis pubis from 2008 to 2013. Topic reviews, case reports, case series, and randomized trials were included for review. STUDY DESIGN: Clinical review. LEVEL OF EVIDENCE: Level 4. RESULTS: Collectively, 188 articles were identified. Of these, 58 were included in this review. CONCLUSION: Based on the available evidence, the majority of these overuse injuries can be managed non-operatively. Primary treatment should include removal from offending activity, normalizing regional muscle strength/length imbalances and nutritional deficiencies, and mitigating training errors through proper education of the athlete and training staff. STRENGTH OF RECOMMENDATION TAXONOMY: C